Kajian Terjemahan Takarir Verdictives Dengan Pendekatan Multi Semiotika - Sulistyo, Chendy; Felayati, Safrina (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2023)
A film has a complex narrative and relates to coherence between the caption (a lingual unit) and moving images (a visual context). A narrative approach is needed in analyzing the film to see the context of the situation when the caption appears in the scene. This is a consideration in making captions so that the translation is acceptable and not literal. The subtitle of this film is studied by looking at the illocution speech acts that are present without consideration in the narrative and audio-visual interplay that plays in it. There have been a lot of research on film subtitles before, but only focused on the linguistic unit. Some of them have tried to see the speech act in film subtitles. The studies that have been carried out have not considered the audio-visual element when the caption appears so that it only sees it as a linguistic unit and only sees the environment linguistically. One form of speech act that appears in the film caption F.R.I.E.N.D.S is the illocution speech act. According to Anggraeni & Sari (2021:213) illocution speech acts are speech acts that aim to state something or also called The Act of Saying Something. The problems studied in this study are; 1) how are the subtitles translated in the F.R.I.E.N.D.S film, 2) how are the subtitles translated in the F.R.I.E.N.D.S film with time constraints. Based on the data analysis that has been carried out, it can be concluded that illocution speech acts are also included in the film's caption but have not considered the visual context. In the film, the role of characters and narrative theory becomes important to be able to express illocution speech acts in conveying their speech